Unico. 2, Hunted - Sattin, Samuel (Graphix, an imprint of Scholastic, 2025)
Still hunted by Venus, Unico befriends a sickly girl imprisoned by an evil robotic machine. Lost in space and time, Unico awakens in an abandoned factory town. Saved by the resourceful mouse, Garapachi, Unico befriends Chiko, a human girl. But he soon learns that a sinister force is at work in the town's factory, bent on killing all living things. Meanwhile, Venus unleashes a fierce hunter who will stop at nothing to find Unico. Can Unico save Chiko? Can the West Wind save Unico?